Nurses And Healthcare Professionals’ Competencies And Readiness For Delivering Digital Diabetes Services In Saudi Arabia: A Systematic Review (The Review of Diabetic Studies, 2025)
Digital health interventions are increasingly integrated into diabetes care globally, enhancing accessibility, patient engagement, and quality of care. In Saudi Arabia, where diabetes prevalence is among the highest worldwide, understanding healthcare professionals’ competencies and readiness to deliver digital diabetes services is essential. This systematic review aimed to synthesize evidence on the knowledge, skills, and readiness of healthcare professionals—including nurses, physicians, pharmacists, radiologists, and social workers—in adopting digital tools for diabetes management. A comprehensive literature search was conducted using PubMed, Scopus, Web of Science, and Google Scholar from 2010 to 2024. Studies included quantitative, qualitative, and mixed-method designs addressing healthcare professionals’ digital health competencies, adoption, and training needs specific to diabetes care. The review was conducted following PRISMA 2020 guidelines, and the Mixed Methods Appraisal Tool (MMAT) was applied for quality assessment. Results from 52 studies indicate that nurses and physicians generally demonstrate moderate digital literacy but face barriers related to insufficient training, high workload, and limited institutional support. Pharmacists and social workers show emerging competence, particularly in teleconsultation and patient education, while radiology staff exhibit readiness in teleimaging and digital diagnostics but require structured training programs. Key facilitators include organizational support, digital infrastructure, and continuous professional development initiatives. Barriers include resistance to change, lack of standardized competencies, and unclear policies. The findings highlight a critical need for tailored training frameworks to strengthen digital health competencies among all healthcare professionals involved in diabetes care. This review underscores the importance of interdisciplinary collaboration and structured competency development to ensure effective adoption and implementation of digital diabetes services in Saudi Arabia. The study provides actionable insights for policymakers, educators, and healthcare institutions aiming to integrate digital health into routine diabetes care and optimize patient outcomes..